Sensitivity loss by Corynespora cassiicola, isolated from soybean, to the fungicide carbendazim - Avozani,Aveline (2014)
Soybean target leaf spot, caused by the fungus Corynespora cassiicola, is controlled especially by leaf application of fungicides. In the last seasons, in the central-west region of Brazil, the disease chemical control efficiency has been low. This led to the hypothesis that the control failure could be due to the reduction or loss of the fungus sensitivity to fungicides. To clarify this fact, in vitro experiments were conducted to determine mycelial sensitivity of five C. cassiicola isolates to fungicides. Mycelial growth was assessed based on the growth of the mycelium on the culture medium, in Petri dishes. The medium potato-dextrose-agar was supplemented with the concentrations 0; 0.01; 0.1; 1; 10; 20 and 40 mg/L of the active ingredients carbendazim, cyproconazole, epoxiconazole, flutriafol and tebuconazole. The experiment was conducted and repeated twice in a controlled environment, temperature of 25±2ºC and photoperiod of 12 hours. Data on the percentage of mycelial inhibition were subjected to logarithmic regression analysis and the concentration that inhibits 50% of the mycelial growth (IC50) was calculated. Loss of sensitivity to carbendazim was observed for three fungal isolates, IC50 > 40 mg/L. Considering all five isolates, the IC50 for tebuconazole ranged from 1.89 to 2.80 mg/L, for epoxiconazol from 2.25 to 2.91, for cyproconazole from 9.21 to 20.32 mg/L, and for flutriafol from 0.77 to 2.18 mg/L. In the absence of information on the reference IC50 determined for wild isolates, the lowest values generated in our study can be used as standard to monitor the fungus sensitivity.